2021
DOI: 10.3390/tropicalmed6010024
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Nipah Virus Infection: Past, Present, and Future Considerations

Abstract: Nipah virus (NiV) is a zoonotic paramyxovirus of the Henipavirus genus first identified in Malaysia in 1998. Henipaviruses have bat reservoir hosts and have been isolated from fruit bats found across Oceania, Asia, and Africa. Bat-to-human transmission is thought to be the primary mode of human NiV infection, although multiple intermediate hosts are described. Human infections with NiV were originally described as a syndrome of fever and rapid neurological decline following contact with swine. More recent outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…The STAT1-binding region of 018 possesses significant sequence similarity to the STAT1binding region of V/W and P proteins from NiV, a paramyxovirus first discovered in Malaysia in 1998 (Chua, 2000). NiV is highly pathogenic and has caused numerous sporadic outbreaks, including recently in Kerala, India (Arunkumar et al, 2019) and no effective treatments or vaccines are available (Hauser et al, 2021). Previous studies of NiV-V showed it sequesters STAT1 and 2 and prevents STAT1 phosphorylation (Rodriguez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The STAT1-binding region of 018 possesses significant sequence similarity to the STAT1binding region of V/W and P proteins from NiV, a paramyxovirus first discovered in Malaysia in 1998 (Chua, 2000). NiV is highly pathogenic and has caused numerous sporadic outbreaks, including recently in Kerala, India (Arunkumar et al, 2019) and no effective treatments or vaccines are available (Hauser et al, 2021). Previous studies of NiV-V showed it sequesters STAT1 and 2 and prevents STAT1 phosphorylation (Rodriguez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The reservoir of NiV is the Pteropus fruit bat and likely gained transmission to humans through pigs. It was first identified in Malaysia in 1998 and has since caused numerous outbreaks in and around South and Southeast Asia (Hauser et al 2021 ; Rathish and Vaishnani 2021 ). The mortality rate of NiV reaches as high 75%.…”
Section: Cross-species Therapeutic Potentials Beyond Sars-cov-2mentioning
confidence: 99%
“…Previously, the NiV disease were found to be linked with consuming date palms juice but now infection has been found in various places with no link to such food habit (McKee et al 2021). Epidemiological studies revealed clustering around household members and hospital contacts without clear animal exposure (Hauser et al 2021). Thus further epidemiological investigations of such case should be properly conducted to avoid epidemics.…”
Section: Introductionmentioning
confidence: 99%